American Neurotology Society, American Otological Society, and American Academy of Otolaryngology – Head and Neck Foundation Guide to Enhance Otologic and Neurotologic Care During the COVID-19 Pandemic. Issue 9 (October 2020) - Kozin, Elliott D.; Remenschneider, Aaron K.; Blevins, Nikolas H.; Jan, Taha A.; Quesnel, Alicia M.; Chari, Divya A.; Kesser, Bradley W.; Weinstein, Jaqueline E.; Ahsan, Syed F.; Telischi, Fred F.; Adunka, Oliver F.; Weber, Peter; et al.
Abstract : N/A: This combined American Neurotology Society, American Otological Society, and American Academy of Otolaryngology – Head and Neck Surgery Foundation document aims to provide guidance during the coronavirus disease of 2019 (COVID-19) on 1) "priority" of care for otologic and neurotologic patients in the office and operating room, and 2) optimal utilization of personal protective equipment. Given the paucity of evidence to inform otologic and neurotologic best practices during COVID-19, the recommendations herein are based on relevant peer-reviewed articles, the Centers for Disease Control and Prevention COVID-19 guidelines, United States and international hospital policies, and expert opinion. The suggestions presented here are not meant to be definitive, and best practices will undoubtedly change with increasing knowledge and high-quality data related to COVID-19. Interpretation of this guidance document is dependent on local factors including prevalence of COVID-19 in the surgeons' local community. This is not intended to set a standard of care, and should not supersede the clinician's best judgement when managing specific clinical concerns and/or regional conditions. Access to otologic and neurotologic care during and after the COVID-19 pandemic is dependent upon adequate protection of physicians, audiologists, and ancillary support staff. Otolaryngologists and associated staff are at high risk for COVID-19 disease transmission based on close contact with mucosal surfaces of the upper aerodigestive tract during diagnostic evaluation and therapeutic procedures. While many otologic and neurotologic conditions are not imminently life threatening, they have a major impact on communication, daily functioning, and quality of life. In addition, progression of disease and delay in treatment can result in cranial nerve deficits, intracranial and life-threatening complications, and/or irreversible consequences. In this regard, many otologic and neurotologic conditions should rightfully be considered "urgent, " and almost all require timely attention to permit optimal outcomes. It is reasonable to proceed with otologic and neurotologic clinic visits and operative cases based on input from expert opinion of otologic care providers, clinic/hospital administration, infection prevention and control specialists, and local and state public health leaders. Significant regional variations in COVID-19 prevalence exist; therefore, physicians working with local municipalities are best suited to make determinations on the appropriateness and timing of otologic and neurotologic care.